Antologizando a Nação: antologias literárias brasileiras, identidade e ideologia no Estado Novo (1937-1945) - Paula Candido Zambelli (Les Cahiers ALHIM)
The anthology genre in Brazil has evolved alongside the construction of a national identity since the 19th century. Originating from undifferentiated editorial objects such as parnasos, florilégios and seletas, in the 20th century anthologies went through a consolidation and specialization driven by the development of a national education, of an editorial market, and, during the Estado Novo (1937-1945), of state policies. Four anthologies, academic and not, from this period were analyzed from the perspective of the complex relationship established between the text and the paratext in this genre. The official project of a rebuilding of the national identity, led by the Ministry of Education and Health, is reflected both in the selection of the literary excerpts anthologized and in the textual apparatus designed to contextualize them. This new entity, characterized by a strong intratextuality, forms a sort of anthological mosaic cemented by the discourse of the nation, thus revealing more about its own time than about a past it pretends to illustrate.